Respuesta :
The answer is C
What you need to do is plug in 3x+2(-3x)=6 then solve for x.
X=-2
C is the only answer with x=-2
What you need to do is plug in 3x+2(-3x)=6 then solve for x.
X=-2
C is the only answer with x=-2
y = −3x
3x + 2y = 6
A) 3x + y = 0
B) 3x + 2y = 6
Multiply A) by -1
A) -3x - y = 0 then add to B
B) 3x + 2y = 6
y = 6
3x + 6 = 0
3x = -6
x = -2
Answer is C
3x + 2y = 6
A) 3x + y = 0
B) 3x + 2y = 6
Multiply A) by -1
A) -3x - y = 0 then add to B
B) 3x + 2y = 6
y = 6
3x + 6 = 0
3x = -6
x = -2
Answer is C